Retrospective study of prenatal ultrasound findings in newborns with a Noonan spectrum disorder. (28th March 2016) - Hakami, Fahad; Dillon, Mitchell W.; Lebo, Matthew; Mason‐Suares, Heather
Abstract: Objectives: Noonan spectrum disorders (NSDs) occur in 1:1000–2500 live births. Currently, there are no guidelines for prenatal molecular genetic testing for NSDs. Recent studies recommend prenatal testing for NSDs when ultrasonography detects two or more associated abnormalities. A stronger association between ultrasound findings and NSDs would enable more informed prenatal genetic testing. Methods: A total of 212 newborns (0–12 weeks) with prenatal ultrasound findings and a clinical suspicion of a NSD were referred for molecular genetic testing. Of these, 159/212 newborns tested had a single ultrasound abnormality and 53/212 newborns had two or more. Testing was performed by either a microarray‐based resequencing assay or next generation sequencing of RAS/MAPK pathway genes associated with NSDs. Prenatal ultrasound findings in positive and negative cases were compared. Results: A disease‐causing variant was identified in 21.7% (46/212) of newborns tested. Of these positive cases, 67.4% (31/46) had only one ultrasound abnormality reported. The rate of detecting a disease‐causing variant in cases with one ultrasound finding was 19.5% (31/159), which was not significantly different ( p ‐value = 0.36) than that in cases with two or more ultrasound findings (28.3%; 15/53). Conclusions: Prenatal molecular testing for NSDs should be considered even in the presence of a single associated abnormal ultrasound finding. © 2016 John Wiley & Sons, Ltd. Abstract : What Is Already Known About This Topic? Certain ultrasonography abnormalities, such as cystic hygroma, increased nuchal translucency, and congenital heart defects, indicate an increased risk of a Noonan spectrum disorder (NSD) in a fetus. Current studies recommend prenatal testing for NSDs only when ultrasonography detected an increased nuchal translucency and at least one additional NSD‐associated abnormality. What Does This Study Add? There is no significant difference in the detection rate of an NSD for fetuses with only one ultrasonography NSD‐associated abnormality versus those with more. A testing strategy in which only fetuses with two or more NSD‐associated abnormalities are tested will reduce the prenatal detection rate.